Board Game: Does it Boost Students’ English Daily Activity Expression Mastery? Permainan Papan: Apakah Permainan Papan Dapat meningkatkan Kemampuan Siswa dalam Mengekspresikan Aktivitas Sehari-hari dalam Bahasa Inggris? - Layyinatul Af"idah; Dian Novita (Academia Open, 2025)
This study aims to determine the effect of using board game in improving seventh-grade students’ English daily activity expression comprehension using the simple present tense. Many students’ experience difficulties in expressing daily activy in English, because of their limited vocabulary, lack of fluency in speaking, and low of self-confidence when constructing sentences.To overcome these issues, a pre-experimental design with a one-group pre-test and post-test was applied. The research involved 23 seventh-grade students from a junior high school in Sidoarjo. The procedure included administering a pre-test, delivering three sessions of treatment using a board game, and conducting a post-test. Students' proficiency in vocabulary, grammar, understanding, fluency, and pronunciation were evaluated using the tests to measure their comprehension regarding the daily activity expression. The data were analyzed using the Wilcoxon Signed Rank Test in SPSS. The results showed a significant increase in students' speaking scores from a mean of 67 in the pre-test to 81 in the post-test, with a significance value of 0.000, indicating the rejection of the null hypothesis. These findings suggest that board game has an impact in enhancing students’ English daily activity expression mastery. Besides improving students’ speaking skills, board game also creates a fun, relaxed atmosphere that motivates students to speak more confidently. Thus, board games can be considered a useful in teaching English expressions, especially in describing daily activity.